Effect of ferrite phase addition on the functional properties of (K0.5Na0.5)NbO3ceramics - Lima, R. J.S.; Banerjee, P.; Araujo, E. B. [UNESP]; Franco, A. (Springer Nature, 2019)
Lead-free ceramics consist of ferroelectric K0.5Na0.5NbO3 (KNN) and spinel ferrimagnetic CoFe2O4 (CFO) phases were prepared by the conventional solid state reaction method. The constituent phase presence of multiferroic material was confirmed by X-ray diffraction techniques with Rietveld refinement methods. A systematic study of dielectric properties at room temperature with frequency revealed that the dispersion is in accordance with the Cole-Cole model with the presence of dc conductivity at lower frequencies. The main reason for this type of dispersion was related with the different heterogeneous conduction mechanism between the ferroelectric and ferrite phases in multiferroic structures. Complex impedance analysis re-established non-Debye type dielectric relaxation mechanism in the multiferroic. The effect of constituents phase variation on the electric and magnetic hysteresis behavior was also examined. The ferroelectric order diluted with the addition of ferrite content. The remnant magnetization (Mr) and saturation magnetization (Ms) values increased while the coercivity (Hc) values of the materialss decreased with the addition of ferrite content. We established that this material is a room temperature multiferroic and highlighted a possible way to modulate functional properties of this lead-free materials for application in microelectromechanical system (MEMS) technology.